Distrihution nsaps of marine nigne from Ihe Iberian Peninsala aad the Balearie lslands. X.Varieties ofFucus spira/is L. and Fi vesiculosas L. (Fuenles, Fucopbyceae) - Gallardo, Tomás; Pérez-ruzafa, Isabel M. (Botanica Complutensis, 1996)
PÉnrz RuzáFá. 1. M. & GALLARDO,T. 1997. Distribuhan inaps of marine algaefram Ihelberian Peninsula and ihe Balearic lslands. Al Vanieties of Fucus spiralis L. and E. vesiculosus L. (Fucales, Fucophyceae). Bar tamplittens¿s 21:121-136. Wc publish here the maps of the distribution along ihe Iberian Peninsula of the varieties of tucas vesicalasus var. vesiculosas, var. campressus, var. linearis, var. vadorum and var valabilis) and E spiralis (var. spiralis, var. timitaneus and van platvcarpas) marine algae ineluded in the Order Fatales> New records are apported.